Characterization of intralaminar mode I fracture of AS4/PPS composite using inverse identification and micromechanics. (December 2016) - Pappas, G.; Canal, L.P.; Botsis, J.
Abstract: A detailed experimental-numerical study of large scale bridging during intralaminar fracture of AS4/PPS uniaxial thermoplastic composite is reported. Identification of bridging tractions is carried out using: (a) An inverse identification method based on quasi-distributed strain data from fiber Bragg gratings, FE modeling and optimization; both small and large displacements are considered in the simulations resulting in negligible differences between the bridging tractions and of about 4% between the energy release rates in the steady state. (b) A micromechanics based virtual testing using the embedded cell approach. Bridging tractions from both methods agree very well and are used in a cohesive model to reproduce fracture. Also the data from these models are used to obtain the energy release rate (ERR) due to bridging. Comparison of these data with experimental ERR values are in good agreement.